Integrated prognostic assessment of apoptosis and chemotherapy related gene in bladder cancer: a prognostic signature - Keyuan Zhao; Gang Xu; Jing Jin; Chao Peng; Jiajun Chen; Yulei Li; Weihao Wang; Shouhua Pan (Discover Oncology)
Abstract Background Bladder cancer (BC), characterized by epithelial heterogeneity, remains a challenging malignancy with limited tissue biomarkers for anticipating neoadjuvant chemotherapy efficacy. Tumor progression, orchestrated by cancer cells, intricately involves the modulation of apoptosis-related pathways. Given their pivotal role in this cascade, apoptosis-related genes emerge as potential determinants of tumor development. Concurrently, the formidable challenge of drug resistance significantly impedes the success of cancer treatments, where a patient's susceptibility to chemotherapy profoundly influences therapeutic outcomes. Consequently, our objective is to develop a prognostic risk model rooted in apoptosis and chemotherapy related gene. This comprehensive approach aims to enhance our ability to predict the prognosis of BC patients and optimize treatment strategies. Methods We extracted 412 BC patients and 19 healthy humans RNA-seq samples from the TCGA database and loaded 1416 apoptosis and chemotherapy related genes from the GeneCards website. Subsequently, we established four risk score models for apoptosis and chemotherapy related genes through single-factor, multi-factor, and LASSO regression analysis. Additionally, we conducted analyses on the risk model using methods such as Kaplan–Meier log-rank test, principal component analysis, time-dependent ROC curve analysis, uni-variate analysis, and multivariate Cox regression analysis. We discussed the relationship of this model with the immune status and its predictive capability for drug sensitivity. Finally, we validated the correlation of these four genes with BC drug resistance by establishing drug-resistant cell lines and conducting in vitro drug resistance-related experiments. Results This study’s findings demonstrate that apoptosis and chemotherapy related genes can impact the progression of BC. We obtained a prognostic risk model composed of four apoptosis and chemotherapy related genes (FASN, GLI2, VHL, and PDGFRA). Among them, FASN, GLI2, and PDGFRA were identified as risk factors, with high expression in the high-risk group, while VHL exhibited high expression in the low-risk group. A nomogram was constructed based on these features to assess patient survival and prognosis. In addition, in vitro drug resistance experiments showed that FASN was associated with BC resistance. Conclusion These four apoptosis-related genes may serve as valuable factors for predicting the prognosis of BC, providing insights into the pathogenic mechanisms of apoptosis-related genes in BC. It provides a new research path to overcome drug resistance in BC. They offer more precise references and guidance for the treatment of high-risk BC patients.